Application De L’ultrason A L’étude De L’homogénéité Des Briques Réfractaires - Djiragbou, N. B. R.; Boffoué, M. O.; Kouadio, K. C.; Kouakou, C. H.; Emeruwa, E. (European Scientific Journal, ESJ, 2017)
The quality of refractory bricks such as their ability to resist to thermal shocks essentially depends on the homogeneity of their structure. The imperfections observed in the structure of some refractory bricks arise from the mode of their preparation. Thus, the homogeneity of bricks manually elaborated with refractory clays and sintered at 1280°C was studied. The speed of ultrasounds in different areas of the bricks was measured with an ultrasound auscultation device. The results point out the speeds of ultrasounds may vary from one zone to another revealing heterogeneities into some bricks. This technique allows showing the distribution of possible heterogeneities in these materials.